Study on sub-regional control of fully mechanized top-coal caving roadway under close irregular goa - LIU Huabo; MENG Fanjing; HUA Shaozhen; WANG Hao (Meikuang Anquan, 2023)
In order to solve the control problems of large deformation of roadway surrounding rock in close coal seams, taking the fully mechanized top-coal caving roadway in close thick coal seams under irregular goaf of Xiaoyu Coal Mine as the engineering background, the test roadway is divided into ordinary section, under the goaf and under the residual coal pillar. The failure characteristics of surrounding rock of coal roadway in different areas are compared and analyzed by geological radar detection, borehole peeping, theoretical calculation and numerical simulation. The results show that: the plastic zone range of fully mechanized top-coal caving roadway in close thick coal seam under irregular goaf is 2.15 m; the influence distance of advanced and violent mining in the coal face is 26 m; the loosening range of the mining side of the roadway is 0.5 m larger than that of solid coal. Based on this, a sub-regional combined control technology of conventional support in general area and strengthened support of channel-steel anchor cable under the goaf and under the residual coal pillar is proposed. The engineering practice shows that the combined support technology can effectively control the large deformation of surrounding rock, and it ensures the safe mining of fully mechanized top-coal caving face.